Optimalisasi Pengelolaan Data dan Laporan Menggunakan Microsoft Excel - Helmiah; Marlina (PASAI : Jurnal Pengabdian kepada Masyarakat, 2024)
Data management and report generation are essential elements in supporting the effective governance of non-formal education institutions such as PKBM Cerdas Mandiri, located in Gampong Lhok Dalam, Peureulak District, East Aceh Regency. However, in practice, administrative management in this institution is still carried out manually, making it prone to errors and time-consuming. This community service project aims to optimize data management and report generation by utilizing Microsoft Excel as the primary tool. The implementation method includes needs assessment, hands-on training (learning by doing), and post-training evaluation. The results show a significant improvement in participants' ability to use Excel’s features such as automated formulas, data validation, chart creation, and pivot tables. Additionally, the training successfully raised awareness of the importance of digitizing administration for work efficiency. The active participation and enthusiasm of the participants indicate that the educational and practical approach is highly effective when applied to community education institutions. This activity demonstrates that Microsoft Excel is a simple yet highly beneficial solution in enhancing professionalism and data management quality within PKBM.